Anaphylaxis during anesthesia: a clinical case - Tutunnyk , A.G.; Mynka , N.V.; Kobelyatskyy , Yu.Yu. (Medicni Perspektivi, 2025)
Adverse events associated with the use of various diagnostic and therapeutic agents are becoming an increasingly urgent and social problem. Anaphylaxis during anesthesia is a rare but life-threatening complication. The incidence of anaphylaxis to cephalosporins according to US researchers was 8 cases per 487,630 cases of parenteral administration of drugs, while cefazolin was the most common cause of perioperative anaphylaxis. Antibiotic prophylaxis is widely used before surgery, but can lead to severe anaphylactic reactions, including anaphylactic shock. The aim of this article was to present a clinical case of anaphylaxis during anesthesia with a description of the symptoms, differential diagnosis and algorithm for providing emergency care, which will allow to deepen the awareness of practicing anesthesiologists about this rare but potentially fatal complication. We present a clinical case of a 32-year-old patient who was scheduled for arthroscopic knee surgery under spinal anesthesia. Upon admission to the operating room, the patient’s condition was assessed as satisfactory. Antibiotic prophylaxis with 2 g of cefazolin was performed. After preloading with isotonic NaCl solution, the patient underwent unilateral spinal anesthesia, which was subsequently assessed as inadequate. As a result, it was necessary to supplement the anesthesia plan with an additional femoral nerve blockade. 5 minutes after the femoral nerve blockade, the patient developed a clinical picture of shock. Intensive therapy included the use of vasopressors (adrenaline) and infusion therapy. As a result of the therapy, the patient’s condition was stabilized and he was discharged from the hospital after 24 hours of observation in the intensive care unit. During the case analysis, it was found that the patient had concealed an episode of a mild anaphylactic reaction to cefazolin in the past. Preventive measures should include the availability of detailed medical documentation of drug allergies, including anaphylaxis. Thus, anesthesiologists should be familiar with the epidemiology, mechanisms of development, clinical cases and treatment of patients with anaphylaxis during anesthesia. The result of the study is a recommendation to practicing anesthesiologists to carefully approach the collection of allergic history, including the possible use of preoperative questionnaires for patients for this purpose, which contributes to a significant reduction in the risks of adverse events during anesthesia care.